Connexin 50 Functions as an Adhesive Molecule and Promotes Lens Cell Differentiation - Zhengping Hu (Nature Portfolio, 2017)
Abstract Connexins play essential roles in lens homeostasis and development. Here, we identified a new role for Cx50 that mediates cell-cell adhesion function. Cx50 enhanced the adhesive capability of AQP0. Interestingly, the expression of Cx50 alone promoted cell adhesion at a comparable level to AQP0; however, this cell adhesive function was not observed with other lens connexins, Cx43 and Cx46. Moreover, the adhesive property occurred in both homotypic with Cx50 expressed in both pairing cells and heterotypic with Cx50 in only one pairing cell, and this function appears to be unrelated to its role in forming gap junction channels. Cx50 KO lenses exhibited increased intercellular spaces between lens fiber cells. The second extracellular loop domain (E2) is primarily responsible for this adhesive function. Treatment with a fusion protein containing E2 domain inhibited cell adhesion. Furthermore, disruption of cell adhesion by the E2 domains impaired primary lens cell differentiation. Five critical amino acid residues in the E2 domain primarily are involved in cell adhesive function as well as lens epithelial-fiber differentiation. Together, these results suggest that in addition to forming gap junction channels, Cx50 acts as an adhesive molecule that is critical in maintaining lens fiber integrity and epithelial-fiber differentiation.